Case Report: Doubts and Pre-occupations About Being Transgender: Questioning One's Gender Identity or a Case of Obsessive-Compulsive Disorder? - Aboujaoude, Elias; Starcevic, Vladan (Frontiers in Psychiatry, 2021)
We report the case of a biological female with gender identity-related doubts possibly masquerading as obsessive-compulsive disorder (OCD). The patient’s parent seemed to favor an OCD explanation for the gender-based self-questioning over acceptance of possible transgender identity. We discuss what OCD is and what it is not in the context of gender identity-based doubt; analogy with the better studied sexual orientation-related OCD; cultural flashpoints around sex and gender that can become the object of OCD; how confusion about biological sex, assigned gender and gender identity can lead to clinical harm; and the role of mental health professionals in fighting the stigma faced by gender minorities.